Odpowiedzi

2009-12-19T22:00:41+01:00
K(x)=W(x)
x(x-a)²=x³-10x²+25x
x(x²-2ax+a²)=x³-10x²+25x
x³-2ax²+xa²=x³-10x²+25x

-2ax²=-10x² I :(-2x²)
a=5

xa²=25x I:x
a²=25 I√
a=5

ODP. Liczba a jest równa 5.
Najlepsza Odpowiedź!
2009-12-19T22:03:08+01:00
K(x)= x(x-a)²
K(x)= x(x²-2ax+a²)
K(x)= x³-2ax²+a²x

W(x)=x³-10x²+25x

K(x)=W(x)
x³-2ax²+a²x=x³-10x²+25x

x³=x³
x³-x³=0
0=0

-2ax²=-10x²
-2ax²+10x²=0
2x²(-a+5)=0 tutaj patrzymy tylko na to, co jest w nawiasie
-a+5=0
-a=-5
a=5

a²x=25x
a²x-25x=0
x(a²-25)=0 tutaj patrzymy tylko na to, co jest w nawiasie
a²-25=0
a²=25
a=√25
a=5



można to też zrobić tak:
x³-2ax²+a²x=x³-10x²+25x
x³-x³-2ax²+10x²+a²x-25x=0
-2ax²+10x²+a²x-25x=0
-2ax²+10x²=0 i a²x-25x=0
2x²(-a+5)=0 i x(a²-25)=0

{-a+5=0
{a²-25=0

{-a=-5
{a²=25

{a=5
{a=5


Odp. a=5

((;